CONNECTION BETWEEN DYNAMICALLY DERIVED INITIAL MASS FUNCTION NORMALIZATION AND STELLAR POPULATION PARAMETERS - McDermid, R; Cappellari, M; Alatalo, K; Bayet, E; Blitz, L; Bois, M; Bournaud, F; Bureau, M; Crocker, A; Davies, R; Davis, T; de Zeeuw, P; et al. (Institute of Physics Publishing, 2014)
We report on empirical trends between the dynamically determined stellar initial mass function (IMF) and stellar population properties for a complete, volume-limited sample of 260 early-type galaxies from the ATLAS3D project. We study trends between our dynamically derived IMF normalization αdyn ≡ (M/L)stars/(M/L)Salp and absorption line strengths, and interpret these via single stellar population-equivalent ages, abundance ratios (measured as [α/Fe]), and total metallicity, [Z/H]. We find that old and alpha-enhanced galaxies tend to have on average heavier (Salpeter-like) mass normalization of the IMF, but stellar population does not appear to be a good predictor of the IMF, with a large range of αdyn at a given population parameter. As a result, we find weak αdyn-[α/Fe] and αdyn -Age correlations and no significant αdyn -[Z/H] correlation. The observed trends appear significantly weaker than those reported in studies that measure the IMF normalization via the low-mass star demographics inferred through stellar spectral analysis. © 2014. The American Astronomical Society. All rights reserved..